SENI TARI KLASIK DULU KINI DAN ESOK - Tjokorda Istri Putra Padmini; Ni Made Arshiniwati (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2023)
Balinese classical dance is an important part of Bali's cultural heritage. However, with the changing times and modern lifestyles, there is a risk that this tradition may erode and not be preserved. Many of the younger generation are more interested in modern things, so maintaining classical dance is a challenge. Balinese classical dance has a strong spiritual dimension. This dance is often used as a means of offering to the gods in the context of religious ceremonies. However, with commercialization and performances for entertainment purposes, the spiritual meaning of this dance can be reduced. This research is a layering of classical dance in the past and regrets of contemporary classical dance as well as an attempt to see the potential for the development of classical dance in the future. Data was collected using a qualitative study by conducting field observations, interviewing informants and reviewing the literature. The results show that classical dance was born in feudal times, the heyday of Javanese and Balinese kings began in the 12th century. Today's classical dance life is supported by changes in society, from a feudal society to an open society. Meanwhile, the art of classical dance in the future will be based on the preservation and development of an artistic aspect, especially dance.Â Keywords: Classical Dance, Preservation and Development